Game Analysis of Endowment Insurance Collection and Supervision Behavior under the Background of Price Reduction - Zhang, Jin (Advances in Social Sciences Research Journal, 2020)
The Central government issued several consecutive articles stressing the need to reduce the contribution rate of endowment insurance and adjust the base of social security contributions. However, can we effectively improve the compliance rate of endowment insurance, and thus increase the actual collection income of endowment insurance through the reform of the fee reduction? What changes will be made to the behavioral decision-making methods among the various subjects, and will it affect the income from the collection of pensions? What kind of supervision is adopted by the central and local governments to promote the increase in the collection of endowment insurance? Based on these problems, this paper adopts the principal-agent game and the three-party evolutionary game model under non-completely symmetric information, analyzes the behavioral decisions of each subject in the process of collection after the fee reduction, and analyzes the influencing factors of dynamic stability and equilibrium. Analysis, and finally, in the context of the endowment insurance fee reduction, the action plan that can effectively increase the income of the endowment insurance collection. The empirical results show that the contribution rate and contribution base of endowment insurance are inversely related to the intensity of local endowment insurance collection, and the reduction of fees can effectively promote the enthusiasm of local governments for collection. When the burden of endowment insurance contributions declines, the enthusiasm of corporate payment has also increased. At the same time, improve the overall level of pensions, promote the openness and transparency of endowment insurance contributions, and strengthen the reward and punishment mechanism in the process of collecting endowment insurance premiums, which can effectively increase the income from endowment insurance collection.